Development Of A Fatigue Model For Hot Mix Modified Asphalt Based On The Critical Temperature Of Asphalt Rheology - Ariyapijati, Raden Hendra (Universitas Mercu Buana, 2024)
External factors that affect the structure of the road pavement are the loads of traffic and the environment (temperature, weather). Fatigue cracking is one of three major distresses for asphalt pavement. One method used for fatigue analysis is classical fatigue. This method is used to obtain an equation model which predicts the service life of a road pavement. Apart from problems like this, there needs to be innovation both in terms of materials and road pavement planning, namely by modifying the asphalt mixture, such as adding buton asphalt and crumb rubber. This research is intended to develop a Monismith model that is used to predict the fatigue life of a road pavement material. Three types of asphalt, namely 60/70 penetration asphalt, buton modified asphalt and crumb rubber modified asphalt were used in this research. The fatigue test used the Four Point Bending Test (4PBT) tools. The specimen which used to fatigue test with 4 variations of asphalt mixtures, 4 variations of temperatures at 15oC, 20oC, 25oC and 30oC. The results of the four-point bending test showed that the Nf value (maximum number of repetitions) at a temperature of 30oC was 394,400 cycles, with 15% crumb rubber modified asphalt. The development of a fatigue model with a critical temperature approach to asphalt mechanistic rheology has resulted from this research.